Common Fixed Point Theorem for Occasionally Weakly Compatible Mappings in Probabilistic Metric Spaces: Sunny Chauhan, Poom Kumam - Team, Support (Thai Journal of Mathematics, 2013)
The aim of this paper is to prove a common fixed point theorem for two pairs of single-valued and set-valued occasionally weakly compatible mappings in Menger spaces. An example is given to illustrate our main result.